Occipito-cervical fusion - Bick, Simon Millard (Department of Health and Rehabilitation Sciences, 2014)
The aim of this study is to review the different surgical indications, techniques and outcomes of occipito-cervical fusion, including C2 fixation methods, the influence on clinical outcome, patient scoring systems and complications.